Influence of Underlying Surface on Distribution of Hourly Heavy Rainfall over the Middle Yangtze River Valley - Yinglian Guo; Jisong Sun; Guirong Xu; Zhiming Zhou; Jizhu Wang (Advances in Meteorology)
The variation of boundary layer circulation caused by the influence of complex underlying surface is one of the reasons why it is difficult to forecast hourly heavy rainfall (HHR) in the middle Yangtze River Valley (YRV). Based on the statistics of high-resolution observation data, it is found that the low resolution data underestimate the frequency of HHR in the mountain that are between the twain-lake basins in the middle YRV (TLB-YRV). The HHR frequency of mountainous area in the TLB-YRV is much higher than that of Dongting Lake on its left and is equivalent to the HHR frequency of Poyang Lake on its right. The hourly reanalysis data of ERA5 were used to study the variation of boundary layer circulation when HHR occurred. It can be found that the boundary layer circulation corresponding to different underlying surfaces changed under the influence of the weather system. Firstly, the strengthening of the weather system in the early morning resulted in the strengthening of the southwest low-level air flow, which intensified the uplift of the windward slope air flow on the west and south slopes of the mountainous areas in the TLB-YRV. As a result, the sunrise HHR gradually increases from the foot of the mountain. The high-frequency HHR period of sunrise occurs when the supergeostrophic effect is weakened, the low-level vorticity and frontal forcing are strengthened, and the water vapor flux convergence begins to weaken. Secondly, the high-frequency HHR period of the sunset is caused by stronger local uplift and more unstable atmospheric stratification, but the enhanced local uplift is caused by the coupling of the terrain forcing of the underlying surface and the enhanced northern subgeostrophic flow, which causes the HHR to start closer to the mountain top at sunset than at sunrise.